Influence of the physico-chemical bioink composition on the printability and cell biological properties in 3D-bioprinting of a liver tumor cell line - Fritschen, Anna; Acedo Mestre, Mariana; Scholpp, Sebastian; Blaeser, Andreas (Frontiers in Bioengineering and Biotechnology, 2023)
The selection of a suitable matrix material is crucial for the development of functional, biomimetic tissue and organ models. When these tissue models are fabricated with 3D-bioprinting technology, the requirements do not only include the biological functionality and physico-chemical properties, but also the printability. In our work, we therefore present a detailed study of seven different bioinks with the focus on a functional liver carcinoma model. Agarose, gelatin, collagen and their blends were selected as materials based on their benefits for 3D cell culture and Drop-on-Demand (DoD) bioprinting. The formulations were characterized for their mechanical (G’ of 10 – 350 Pa) and rheological (viscosity 2 – 200 Pa*s) properties as well as albumin diffusivity (8 – 50 µm2/s). The cellular behavior was exemplarily shown for HepG2 cells by monitoring viability, proliferation and morphology over 14 days, while the printability on a microvalve DoD printer was evaluated by drop volume monitoring in flight (100 – 250 nl), camera imaging of the wetting behavior and microscopy of the effective drop diameter (700 µm and more). We did not observe negative effects on cell viability or proliferation, which is due to the very low shear stresses inside the nozzle (200 – 500 Pa). With our method, we could identify the strengths and weaknesses of each material, resulting in a material portfolio. By specifically selecting certain materials or blends, cell migration and possible interaction with other cells can be directed as indicated by the results of our cellular experiments.